Individual differences in adults' second language fluency development: Motivation and language use - Kahng, Jimin (Frontiers in Communication, 2022)
Utterance fluency (UF) in a second language (L2) has been found to be associated with L2 proficiency. Nevertheless, the longitudinal development of UF has been underexamined and its relationship with individual differences such as motivation and L2 use has rarely been investigated simultaneously. The current study investigated L1-Chinese L2-English speakers’ changes in UF (speed, pausing, and repair phenomena) before and after five-month study-abroad and related UF changes to L2 use and motivation based on L2 Motivational Self System (Dörnyei, 2009). The results showed that participants improved in mean syllable duration and end-clause silent pausing. Individuals’ changes in certain UF measures, such as mean syllable duration and mid-clause pause frequency, were positively correlated with daily use of L2. Motivation measures largely did not exhibit significant correlations with UF changes, whereas ideal L2 self and intended effort/commitment demonstrated significant positive relationships with daily L2 use.